The peak player load™ of state-level netball matches. Issue 2 (February 2020) - Graham, Scott; Zois, James; Aughey, Robert; Duthie, Grant
Abstract: Objectives: To investigate the peak accelerometer-derived intensity of state-level netball matches and compare differences between positional groupings. Findings will provide guidance for sport science professionals on how to best replicate the most intense passages of play in training settings. Design: Longitudinal (one season). Method: Twenty-eight netball athletes across three teams from the same club wore an accelerometer (S5 Optimeye, Catapult sports) for all matches, in one season. Raw acceleration data were downloaded and converted into a vector magnitude (Player Load™) we then quantified the peak intensity over 30-s and one to ten-minute time periods. Positional groupings were created based on the number of thirds on a netball court that a particular position can enter, as this was deemed more appropriate for the current study than the traditional combinations based on tactical requirements. A linear mixed-model with fixed and random effects was utilised along with magnitude-based inferences to determine meaningful differences with 90 % confidence limits (CL). Results: Across all time periods post 30-s, only one comparison was not meaningfully different i.e. three-thirds v two-thirds at the one-minute timepoint (effect size: 0.27, CL −0.05 to 0.60). Conclusions: Findings justify that netball athletes, depending on positional group defined by this study, should train at different intensities dependent on a specified duration. Conditioning professionals and coaches should design training drills that best replicate the peak intensity of match play. This may improve an athlete's physical performance capacity during highly exertive periods of competition, which regularly occur at critical moments in play.